Transcriptome sequencing of Brassica napus highlights the complex issues with soil supplementation with sewage sludge. (July 2022) - Jaskulak, Marta; Rostami, Saeid; Zorena, Katarzyna; Vandenbulcke, Franck
Abstract: The soil supplementation with sewage sludge (SS) has become a widespread method to improve soil quality, but its long-term possible consequences are still relatively unknown. SS may contain several groups of contaminants to which the biological responses of the organisms are still poorly understood mainly due to the mixture toxicity. In this context, RNA-seq has been used to assess the impact of the exposure to sewage sludge supplemented soil at the whole-transcriptome level in the Brassica napus (B. napus) . Although the municipal sewage sludge passed all safety regulations set by the EU commission (86/278/EEC), soil supplementation with SS caused a significant (p < 0.05) increase in the content of lead (by 68.8%, 71.4% in plant shoots and roots, respectively), zinc (by 22.4% and 31.2%), nickel (by 67.0% and 30.2%), and copper (by 33.1% and 39.2%). The de-novo assembled transcriptome of B. napus identified 555 differently expressed genes (DEGs) in a response to sewage sludge supplementation at the false detection rate below 0.001 (FDR <0.001). Among them, 313 genes were up-regulated and 242 genes were down-regulated. The gene ontology analysis (GO) had shown, that significantly enriched GO groups included genes involved in photosynthesis, carbohydrate metabolism and photosystems repair (41 genes), response to oxidative stress (50 genes), response to pathogens (36 genes), response to xenobiotics (15 genes), and heavy metals (41 genes), cell death (8 genes), cell wall structure (15 genes). These results suggest a significant impact of contaminants in sewage sludge on plants transcriptome. The transcriptomic approach facilitated a better understanding of the molecular level of the potential toxicity of sewage sludge in B. napus . RNA-seq allowed for the identification of potential novel early-warning molecular markers of environmental contamination. This work highlights the crucial necessity for rapid legislation change concerning the allowable levels of contaminants in sewage sludge applied on land, to mitigate the possible adverse outcomes in the ecosystem after its use as a fertilizer. Graphical abstract: Image 1 Highlights: Soil supplementation with SS upregulated genes involved in oxidative stress in B. napus . 313 unigenes were identified as upregulated by SS supplementation, and 242 were downregulated. SS altered expression of genes involved in response to pathogens, xenobiotics, and heavy metals. Other DEGs are involved in photosynthesis, photosystem repair, and carbohydrate metabolism.